Exceptional foraging plasticity in King Penguins (Aptenodytes patagonicus) from a recently established breeding site in Tierra del Fuego, Chile - Pütz, Klemens (2021)
Animals constantly test the borders of their own ecological niche and tend to expand their range, which is now additionally challenged by global climate change. Following human exploitation throughout the Southern Ocean in the 19th and the beginning of the 20th century, numbers of King Penguin breeding pairs have increased and former breeding sites have been re-colonized. Since 2010 a breeding colony became (re-)established at Bahía Inútil, Strait of Magellan, Tierra del Fuego, Chile. The aims of this study were to study the foraging ecology of King Penguins at this new breeding site, which is characterized by a set of different environmental variables as it is located within the confined environment of the Magellan Strait, more than 300 km from the open ocean. During the course of this study, thirty-two birds were successfully equipped with external devices that recorded 206 foraging trips by breeding and non-breeding birds. With one exception, all birds foraged throughout the year exclusively in the Magellan Strait with the main foraging areas located within 100 km from the colony. The diving activities of 15 King Penguins were recorded during 59 foraging trips, the deepest dive was 160 m and the longest dive lasted 6.75 mins. Based on a representative subsample of 3000 dives, mean dive depth was 32 ± 34 m and mean dive duration 117 ± 84 s. Accordingly, foraging trip durations throughout the year were significantly shorter than those recorded for conspecifics elsewhere. In accordance with these changes in foraging behavior, stomach contents from seven birds showed a mix of fish and squid, with Falkland sprats Sprattus fuegensis as the main prey item present in all samples. The implications of these behavioral adaptations are discussed with regard to this unusual confined foraging environment and predicted changes in the performance of King Penguins breeding elsewhere following global change.